The Mnemonic Functions of Physics Wall - Kent C. Bloomer (Oz, 1990)
The ornaments for a new atrium at the center of the Physics Campus, at the University of Oregon, were proposed in a national competition of designs to be incorporated in that space. I was awarded the commission to design and build a scheme for a wall to memorialize the purpose of a central academic gathering place inspired by John Moseley.